2005
DOI: 10.32468/be.334
|View full text |Cite
|
Sign up to set email alerts
|

Derivative markets impact on colombian monetary policy

Abstract: Derivatives are contingent claims that complete financial markets. Their use allow agents and firms to ameliorate the impact over consumption, production and investment given a change in relative prices induced by an active monetary policy. In this sense, derivatives generate in some cases a loss in the effectiveness of the traditional monetary transmission channels in the short run, and in others, they promote an increase in the speed of transmission itself. Using an investment model, the impact of the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Kashyap and Stein (2000) revealed that the influence of monetary policy on credit behavior is larger for banks with little liquid balance-sheets, supporting the bank credit channel of transmission of monetary policy. As per Gómez-González et al (2005), the basic monetary policy transmission channels have been partially diluted, which lowers effectiveness of monetary policy in the short run in impacting real variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kashyap and Stein (2000) revealed that the influence of monetary policy on credit behavior is larger for banks with little liquid balance-sheets, supporting the bank credit channel of transmission of monetary policy. As per Gómez-González et al (2005), the basic monetary policy transmission channels have been partially diluted, which lowers effectiveness of monetary policy in the short run in impacting real variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Kashyap and Stein (1997; discovered that the channel will come into effect through its influence on loan supply especially when the bank has less liquid balance sheet. Gomez et al (2005) concluded that monetary policy loses some effectiveness in influencing real variables in the short run, due to the partial dilution of the main monetary transmission channels. Mishra et al (2012) found that the channel of monetary transmissions tend to be dominated by bank lending rate channel for low income countries with low level of FD.…”
Section: Literature Reviewmentioning
confidence: 99%